Optogenetic dissection of Rac1 and Cdc42 gradient shaping. Issue 1 (December 2018) - Beco, S.; Vaidžiulytė, K.; Manzi, J.; Dalier, F.; Federico, F.; Cornilleau, G.; Dahan, M.; Coppey, M.
Abstract During cell migration, Rho GTPases spontaneously form spatial gradients that define the front and back of cells. At the front, active Cdc42 forms a steep gradient whereas active Rac1 forms a more extended pattern peaking a few microns away. What are the mechanisms shaping these gradients, and what is the functional role of the shape of these gradients? Here we report, using a combination of optogenetics and micropatterning, that Cdc42 and Rac1 gradients are set by spatial patterns of activators and deactivators and not directly by transport mechanisms. Cdc42 simply follows the distribution of Guanine nucleotide Exchange Factors, whereas Rac1 shaping requires the activity of a GTPase-Activating Protein, β2-chimaerin, which is sharply localized at the tip of the cell through feedbacks from Cdc42 and Rac1. Functionally, the spatial extent of Rho GTPases gradients governs cell migration, a sharp Cdc42 gradient maximizes directionality while an extended Rac1 gradient controls the speed. A steep gradient of Cdc42 is at the front of migrating cells, whereas the active Rac1 gradient is graded. Here the authors show that Cdc42 gradients follow the distribution of GEFs and govern direction of migration, while Rac1 gradients require the activity of the GAP β2-chimaerin and control cell speed.